The Problems of Addressing Microclimate Factors in Urban Planning of the Subarctic Regions. (June 2015) - Ebrahimabadi, Saeed; Nilsson, Kristina L; Johansson, Charlotta
Urban life in the towns of the subarctic regions is affected by the severity of the local climate, which must be taken into account in urban planning. Previous studies show that the use of climate knowledge in urban planning is hindered by different constraints. In this study we focus specifically on the problems of incorporating microclimate factors into the urban planning practices in northern Sweden. We rely on a literature study and focus on interviews as our study methods. Some of the major problems identified are the lack of design knowledge relevant to a cold climate, lack of user-friendly tools to analyze microclimate, overlooking the potential uses of local climate, and lack of support from politicians. The problems related to knowledge development and the lack of tools for microclimate analysis are discussed further. In terms of knowledge issues, the planners' awareness of climate objectives achievable at different planning scales needs to be improved. There should be further research into the effect of urban form on the use of snow and on snow-removal activities. Tools for microclimate analysis should become more user friendly for planners. More importantly, planners need methods that combine different microclimate analyses and offer a complete assessment of a given design scheme.